Polysaccharides from Sargassum tenerrimum: structural features, chemical modification and anti-viral activity - Sinha, Sharmistha; Astani, Akram; Ghosh, Tuhin; Schnitzler, Paul; Ray, Bimalendu (Phytochemistry, 2010)
Herpes simplex viruses (HSVs) display affinity for cell-surface heparan sulfate proteoglycans with biological relevance in virus entry. Here, we exploit an approach to inhibiting HSV infection by using a sulfated fucoidan, and a guluronic acid-rich alginate derived from Sargassum tenerrimum, mimicking the active domain of the entry receptor. These macromolecules have apparent molecular masses of 30±5 and 26±5kDa, respectively. They and their chemically sulfated derivatives showed activity against herpes simplex virus type 1 (HSV-1). Their inhibitory concentration 50% (IC50) values were in the range 0.5-15μg/ml and they lacked cytotoxicity at concentrations up to 1000μg/ml. The anti-HSV activity increased with increasing sulfate ester content. Our results suggest the feasibility of inhibiting HSV infection by blocking viral entry with polysaccharide having specific structure.